2009
DOI: 10.5459/bnzsee.42.4.288-301
|View full text |Cite
|
Sign up to set email alerts
|

Determination of structural irregularity limits

Abstract: Structures may be irregular due to non-uniform distributions of mass, stiffness, strength or due to their structural form. For regular structures, simple analysis techniques such as the Equivalent Static Method, have been calibrated against advanced analysis methods, such as the Inelastic Dynamic Time-History Analysis. Most worldwide codes allow simple analysis techniques to be used only for structures which satisfy regularity limits. Currently, such limits are based on engineering judgement and lack proper ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 8 publications
4
23
0
Order By: Relevance
“…For multistorey structures, ISD w_flex increases with decreasing structural height, making the first storey critical. This can be expected for structures having equal storey stiffness at all the storeys [29]. Figure 7 shows the increase in total displacement at midspan because of different diaphragm flexibility ratios.…”
Section: Elastic Dynamic Time-history Analysessupporting
confidence: 92%
See 3 more Smart Citations
“…For multistorey structures, ISD w_flex increases with decreasing structural height, making the first storey critical. This can be expected for structures having equal storey stiffness at all the storeys [29]. Figure 7 shows the increase in total displacement at midspan because of different diaphragm flexibility ratios.…”
Section: Elastic Dynamic Time-history Analysessupporting
confidence: 92%
“…Conduct dynamic time-history analyses by subjecting the structure to a suite of earthquake ground motions. In this paper, 20 SAC (SEAOC-ATC-CUREE) LA records with probabilities of exceedance of 10% in 50 years [29] are used for all the dynamic analyses. Figure 3 shows the response spectra for the record suite.…”
Section: Analysis Methodologysupporting
confidence: 84%
See 2 more Smart Citations
“…This approach has been used in a number of publications (e.g., Tagawa et al [10], MacRae et al [11], Sadashiva et al [12], Tagawa et al [13], and MacRae [14]). Earlier studies [9][10][11][12][13][14] on structural modeling have shown that the frames modeled as a combination of vertical shear column and a vertical continuous column (flexural column) can represent the behavior of real structures well. The flexural column represents all continuous columns throughout the whole structure.…”
Section: Modeling and Evaluation Approachmentioning
confidence: 99%